The Role of Advanced Imaging in Gout Management - Li, Shuangshuang; Xu, Guanhua; Liang, Junyu; Wan, Liyan; Cao, Heng; Lin, Jin (Frontiers in Immunology, 2022)
Gout is a common form of inflammatory arthritis where urate crystals deposit in joints and surrounding tissues. With the high prevalence of gout, the standardized and effective treatment of gout is very important, but the long-term treatment effect of gout is not satisfied because of the poor adherence in patients to the medicines. Recently, advanced imaging modalities, including ultrasonography (US), dual-energy computed tomography (DECT), and magnetic resonance imaging (MRI), attracted more and more attention for their role on gout as intuitive and non-invasive tools for early gout diagnosis and evaluation of therapeutic effect. This review summarized the role of US, DECT, and MRI in the management of gout from four perspectives: hyperuricemia, gout attacks, chronic gout, and gout complications described the scoring systems currently used to quantify disease severity and discussed the challenges and limitations of using these imaging tools to assess response to the gout treatment.